Diseño de un equipamiento comunitario de producción agrícola y comercialización, mediante el análisis de accesibilidad de desiertos alimenticios para abastecer de productos orgánicos en bellavista de Caranqui, Ibarra - Calderón Pita, Bryan Alexander (2024)
The present thesis work is developed in the southern part of the city of Ibarra, Imbabura province, where due to a lack of planning, there is a highly productive area and a lack of public spaces for generating commerce. Additionally, there is the consumption of resources by users who need to travel to the city center to engage in the buying or selling of food. Furthermore, as a result of constant territorial and population growth, Bellavista de Caranqui, a peripheral area, has experienced morphological changes and changes in land use. Supported by the collection of literary information (journals, books, research articles, and websites), concepts, regulations, and qualitative methodologies (data sheets and interviews) as well as quantitative methods (indices and surveys) are established. Additionally, in order to obtain characteristics, qualities, and criteria for the design of the proposal, field visits and surveys are conducted. At the urban scale, the proposal aims to enhance the functional and scenic mobility of the surrounding area by promoting local activities. By encompassing concepts such as productive activity, local commerce, and the ecological environment, it is necessary to integrate a community facility that addresses the existing food supply issues in the area, increasing local economic activity by offering quality job opportunities for all. Furthermore, it should significantly reduce the ecological footprint and embrace sustainability criteria.